Ethno Religious Conflict and Settlement Pattern in Northern Nigeria - Gambo, Y. L.; Omirin, M. M. (Richtmann Publishing, 2012)
The preponderance of violent ethno religious fracas in Nigeria, especially in Northern part of the country, has acquired such adreadful level of reoccurrence. This violent insurgence has started taking its toll on the response and organization of the real propertymarket. The study seeks to examine the influence of ethno religious conflict on settlement patter of some selected cities in NorthernNigeria. Empirical survey revealed that the level of notoriety it has acquired has shaped and influenced the real property marketenterprise and ushered in settlement pattern along religious and in some cases ethnic lines. This development has negative impact onland use and administration as some activities are inaccessible in some areas of dominant religion. Government and community leadersshould checkmate this hideous development which is fast-spreading and can dramatically disrupts land use planning, spill over bordersand reduce growth and prosperity across entire regions.